2021
DOI: 10.5935/1415.2762.20210035
|View full text |Cite
|
Sign up to set email alerts
|

Continuidade Do Cuidado Em Saúde: Análise Da Produção De Teses E Dissertações Brasileiras

Abstract: RESUMO Objetivo: analisar como têm se configurado as interpretações sobre a continuidade do cuidado em dissertações e teses da área da saúde no Brasil. Método: estudo documental de abordagem quantitativa. Busca realizada em janeiro de 2021 a partir do termo “continuidade do cuidado” na base de dados Catálogo de Teses e Dissertações da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior. Incluíram-se 28 trabalhos, 21 dissertações e sete teses publicadas até 2019. Para análise dos dados foram utilizadas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
5
0
4
Order By: Relevance
“…In southern Brazil, a study of patients with chronic diseases reported a moderate CT score 11 . In Brazil, CT strategies are being constructed and adapted; no studies have tested the effectiveness of actions that can be performed during hospitalizations 12,13 . As a result, studies at the national level are limited.…”
mentioning
confidence: 99%
“…In southern Brazil, a study of patients with chronic diseases reported a moderate CT score 11 . In Brazil, CT strategies are being constructed and adapted; no studies have tested the effectiveness of actions that can be performed during hospitalizations 12,13 . As a result, studies at the national level are limited.…”
mentioning
confidence: 99%
“…The definition of continuity of care was presented in only 53.6% of studies assessed. This can lead to the adoption of other terms in a similar way, influencing the interpretation of studies ( 5 ) .…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the mismatch between the increase in chronic health conditions and work and management processes focusing on acute or chronic-acute conditions also demonstrate the fragmentation of care. To qualify care management and ensure continuity of care in different services, the Unified Health System (SUS – Sistema Único de Saúde ) is organized in RAS, horizontally between different points of care, with different technological densities, with Primary Health Care (PHC) being the care coordinator ( 5 ) . This organization in networks, however, still encounters difficulties in several aspects related to operationalization, (dis)articulation of network points and adoption of a care model that aims at comprehensive care.…”
Section: Introductionmentioning
confidence: 99%
“…A definição de continuidade do cuidado foi apresentada em apenas 53,6% dos trabalhos avaliados. Isso pode levar à adoção de outros termos de maneira similar, influenciando a interpretação dos estudos (5) .…”
Section: Introductionunclassified
“…No Brasil, o descompasso entre o aumento de condições crônicas de saúde e processos de trabalho e a gestão com enfoque nas condições agudas ou crônico-agudizadas demonstram ainda a fragmentação da assistência. Para qualificar a gestão do cuidado e garantir a continuidade da assistência nos diferentes serviços, o Sistema Único de Saúde (SUS) organiza-se em RAS, de maneira horizontal entre diferentes pontos de atenção, com diferentes densidades tecnológicas, sendo a Atenção Primária à Saúde (APS) a coordenadora do cuidado (5) . Essa organização em redes, no entanto, ainda encontra dificuldades em diversos aspectos relacionados à operacionalização, (des)articulação dos pontos da rede e adoção de um modelo de atenção que vise à integralidade do cuidado.…”
Section: Introductionunclassified